Levelized cost of electricity considering electrochemical energy storage cycle-life degradations. (February 2019) - Lai, Chun Sing; Locatelli, Giorgio; Pimm, Andrew; Li, Xuecong; Lai, Loi Lei
Abstract: Electrochemical Energy Storage (EES) will be a crucial asset to support the increasing high penetrations of intermittent renewables and to provide means for energy arbitrage. From the investment perspective, the economics for energy systems with EES can be challenging to appraise due to not being an electrical generator. This work examines the system's Levelized Cost of Electricity (LCOE) for a Photovoltaic (PV), Anaerobic Digestion biogas power plant (AD) and EES hybrid energy system in Kenya. By excluding degradation costs at scenarios with high EES capital costs, it is learned that the lowest LCOE can be achieved when EES is given dispatch priority over AD. This appears to be the opposite when degradation cost is included. For more accurate economic analysis, the future research areas are identified as follows: techno-economic analysis needs to consider storage degradation at different operating conditions; and storage degradation models that consider various temperature, C-rate, and state of charge, calendar ageing are required. When comparing energy storage options, cell degradation for EES is an important factor to be addressed in a techno-economic analysis for Generation Integrated Energy Storage (GIES) and non-GIES systems.